Kinerja profitabilitas Bank Mega Syariah berdasarkan analisis Return on Assets (ROA) tahun 2020–2024 - Afifah, Diah Ayu (Maliki Interdisciplinary Journal, 2025)
Profitability is one of the main indicators in assessing a bank’s financial performance, including Bank Mega Syariah, a sharia financial institution that plays a role in supporting the stability of the national financial system. Return on Assets (ROA) is used as an important ratio to measure a bank’s ability to generate profits based on total assets managed. This study aims to analyze the development of Bank Mega Syariah’s ROA during the 2020–2024 period and assess the effectiveness of asset management in generating profitability. The research method uses a quantitative descriptive approach through secondary data analysis in the form of the bank’s annual financial reports. The results show that Return on Assets (ROA) experienced significant fluctuations: a sharp increase in 2021, a decrease in 2022, then stabilizing at around 1.5 percent during 2023–2024. This pattern indicates that the bank’s profitability is not yet consistent and is still influenced by changes in net profit and asset growth dynamics. Overall, Bank Mega Syariah has been able to maintain stable profitability in the past two years, but the Return on Assets (ROA) value remains at a moderate level, requiring optimization of productive asset management and operational efficiency to achieve more ideal profitability standards.